Determining the main factors impacting the differences between soil and air temperatures over China - Xiqiang Wang; Rensheng Chen; Hongyuan Li (International Journal of Climatology, 2022)
Knowledge of the difference between soil and air temperatures (Δ T ) is helpful to improve our understanding on the land‐atmosphere thermal interactions and temperature‐dependent soil processes. Based on 272 stations across China, this study investigated the spatiotemporal variations of the annual and seasonal Δ T (difference between soil temperature at a depth of 0.4 m and air temperature) from 1981 to 2014, and quantified the relative contributions of multiple environmental variables (snow cover, precipitation, vegetation, soil moisture, and solar radiation) to Δ T variation for the first time. Air temperature primarily controls soil temperature dynamics, but the asynchronous trends of soil and air temperatures may lead to the complexity of the land‐atmosphere relationship. Almost no apparent trends in Δ T were detected for the entire China (except in summer), but the spatial heterogeneity of trends was evident. Snow cover conditions greatly dominated the Δ T dynamics both annually and seasonally (except in summer). The relative contribution of snow cover duration to Δ T variation was significantly greater than that of mean snow depth for the entire China, but the regional differences in the contributions of the two variables were noticeable at different seasons. The greening of vegetation closely associated with the Δ T variation in annual, autumn and winter, and soil moisture exerted a great influence on summer Δ T , associated with sunshine duration (a proxy for surface solar radiation). The amount of precipitation made a slight impact on Δ T at either seasonal or annual scales.